Penggunaan Jar Test untuk Penentuan Dosis dan Komposisi Optimum Komposit Koagulan Poly Aluminium Chloride (PAC) – Kitosan dalam Menurunkan TSS dan COD - Afiuddin, Ahmad Erlan; Astuti, Ulvi Pri; Dewi, Tanti Utami; Apriani, Mirna; Mayangsari, Novi Eka; Jannah, Nabillah Rodhifatul (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
Laundry waste is a pollutant that has pollutant parameters such as TSS and COD. One alternative processing is flocculation-coagulation using synthetic coagulants. The advantage of synthetic coagulants is that they are able to remove high concentrations of pollutants, but the disadvantages are that they produce quite a lot of chemical sludge and the pH of the water becomes acidic because the higher the concentration, the more coagulant is used. Previous research explains that chitosan at low doses has good penyisihan efficiency so that when combined with PAC it is hoped that it can increase penyisihan efficiency with less sludge. The purpose of this study was to determine the optimum dosage and composition for PAC and chitosan coagulant composites using the Jar Test. The Jar Test method for determining the optimum dose uses fast stirring at 140 rpm for 2 minutes and then slow stirring at 60 rpm for 15 minutes and settling for 30 minutes. Determination of the optimum dose by adding a coagulant composite of 300 ppm, 500 ppm, and 700 ppm and by varying the composition at each dose, namely 1:1, 1:3, and 3:1 between PAC-chitosan. The best conditions from the study obtained an optimum dose of 700 ppm and an optimum composition of 3:1 between PAC and chitosan resulting in COD and TSS penyisihan efficiencies of 70.04% and 90.82%.